Application of New Media Big Data in Visual Performance of Axonometric Illustration - Jia Zhou (Applied Bionics and Biomechanics)
With the rapid development of Internet technology today, especially in the fields of new media, digital TV, digital movies, smartphones, smart hardware, mobile Internet and big data, new media forms bring us a shocking sensory experience. Axonometric illustration, a traditional and modern artistic expression, is becoming more and more attractive in the new media era. Today, with the continuous progress of science and technology, the continuous innovation of thinking, and the rapid improvement of public aesthetics, traditional axonometric illustrations have been unable to adapt to the gradual improvement of people’s needs for artistic aesthetics. This paper will start from the research background of “new media” and combine the characteristics of the axonometric illustration industry itself. On the basis of analyzing related theories at home and abroad, the literature research method and algorithm-driven method are used comprehensively. It can not only effectively improve the visual effect of axonometric illustration by 12.3% but also solve the problems and challenges faced by the current China’s axonometric illustration industry.